The Diagnostic Value of SCUBE1 in Unstable Angina Pectoris Patients - OZKAN, Abuzer; Sonmez, ERTAN; SÖNMEZ, ERTAN; OZDEMIR, Serdar; Ozer, Omer Faruk; ÖZER, ÖMER FARUK; MUHARREM, Nasifov; Gulen, BEDİA; GÜLEN, BEDİA; KESKIN, Muhammed (My University, 2016)
Aim: Signal peptide complement C1r/C1s, Uegf, and Bmp1-epidermal growth factor-like domain-containing protein 1 (SCUBE1) has been used in research as a biomarker in acute coronary syndrome (ACS). The aim of this study is to determine if SCUBE1 and routine laboratory parameters are effective in distinguishing the patients presenting with clinical symptoms of unstable angina pectoris (USAP) from the patients who have non-ST-segment elevated myocardial infarction (NSTEMI) and non-cardiac chest pain patients (NCCP).